Analysis of Consumer Behavior and The Impact of Increased Use of Online Shop Businesses in Makassar - Nahriana, Nahriana (Cita konsultindo, 2023)
This research aims to determine consumer behavior and the impact of increased use of online shops in the Makassar area during the Covid-19 pandemic. This research will discuss behavioral theory, consumer behavior, purchasing decisions, and online business. This research was conducted using a qualitative narrative approach and used the problem study method to share results. The problem study method is an in-depth and detailed investigation of an incident and can be an incident, environment, or exclusive situation that discusses or means something. Researchers conducted research on online shop users until they received saturated data and found answers that depended on the research subject. Data analysis used in this research includes organizing data, reading data (memos), writing data into code, grouping into coding topics, interpreting data, and presenting data (Cresswell, 2018). Based on the research results, there are two discussions, namely Consumer Behavior in Online Shopping and the Impact of Increasing Use of Online Shop Businesses.